PENERAPAN MODEL PEMBELAJARAN CHALLENGE BASED LEARNING TERHADAP HASIL BELAJAR KOGNITIF PADA MATERI KALOR DI SMAN 1 KUALA KAMPAR - Isnaini, Isnaini; Ma’ruf, Zuhdi; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The aim to be achieved from writing this thesis is to improve students' cognitive learning outcomes in heat material at SMAN 1 Kuala Kampar. It is hoped that this research can help teachers to convey learning using other learning models, not only learning using the conventional model which makes students bored of paying attention when the teacher teaches, so by using the CBL model it is hoped that it can improve student learning outcomes which were previously low using the conventional model. Research on the application of the CBL learning model to cognitive learning outcomes in heat material was carried out at SMAN 1 Kuala Kampar in the odd semester 2024/2025. The application of this model uses a descriptive research model with a quantitative approach. To find out the students' learning outcomes, the researchers provided a questionnaire which was given to 25 students. Researchers distributed pretest questions before using the CBL learning model, and posttest questions after using the CBL learning model. Then, after giving questions to the students, it was found that the average pretest score was 57.5 while the posttest score was 75. The median pretest score was 55 while the posttest was 75. The pretest mode score was 50 while the posttest was 85. Based on the research results, it was concluded that the comparison of the pretest and posttest scores experienced an increase after using the Challenge Based Learning learning model, it was found that the average pretest score was 57.4 and the average posttest score was 75.Key Words: learning model, challenge based learning, cognitive learning outcomes.